Consumer Purchase Decision On Teakwood Furniture In Klang Valley - Arjunan, A. Ravendiran (2007)
The study examines the purchase decision of teakwood furniture buyers n the Klang Valley. The hypothesis testing was conducted to find out whether purchase decision of the buyers is influenced by 4 independent variables. The variables are the durability, design, price and esteem.